Compensatory growth of congenital solitary kidneys in pigs reflects increased nephron numbers rather than hypertrophy. - Stefan H van Vuuren (Public Library of Science (PLoS), 2012)
Background Patients with unilateral MultiCystic Kidney Dysplasia (MCKD) or unilateral renal agenesis (URA) have a congenital solitary functioning kidney (CSFK) that is compensatory enlarged. The question whether this enlargement is due to increased nephron numbers and/or to nephron hypertrophy is unresolved. This question is of utmost clinical importance, since hypertrophy is associated with a risk of developing hypertension and proteinuria later in life with consequent development of CKD and cardiovascular disease. Methodology/principal findings In a cohort of 32,000 slaughter pigs, 7 congenital solitary functioning kidneys and 7 control kidneys were identified and harvested. Cortex volume was measured and with a 3-dimensional stereologic technique the number and volume of glomeruli was determined and compared. The mean total cortex volume was increased by more than 80% and the mean number of glomeruli per kidney was 50% higher in CSFKs than in a single control kidney, equaling 75% of the total nephron number in both kidneys of control subjects. The mean total glomerular volume in the CSFKs was not increased relative to the controls. Conclusions/significance Thus, in pigs, compensatory enlargement of a CSFK is based on increased nephron numbers. Extrapolation of these findings to the human situation suggests that patients with a CSFK might not be at increased risk for developing hyperfiltration-associated renal and cardiovascular disease in later life due to a lower nephron number.